2016
DOI: 10.15807/jorsj.59.241
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Geometrical Analysis of Weakly Infeasible SDPS

Abstract: In this article, we develop a detailed analysis of semidefinite feasibility problems (SDFPs) to understand how weak infeasibility arises in semidefinite programming. This is done by decomposing a SDFP into smaller problems, in a way that preserves most feasibility properties of the original problem. The decomposition utilizes a set of vectors (computed in the primal space) which arises when we apply the facial reduction algorithm to the dual feasible region. In particular, we show that for a weakly infeasible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…A chain of faces of K is a finite sequence of faces satisfying F 1 · · · F and the length is defined to be . For the SDP case, they showed that the bound can be refined to S n + − 2, which matches the bound discussed in [7], since S n + = n + 1. If K = K n 1 × · · · × K n m , then the largest chain of faces of K * has length 2m + 1.…”
Section: The Number Of Directions Needed To Approach Ksupporting
confidence: 72%
See 2 more Smart Citations
“…A chain of faces of K is a finite sequence of faces satisfying F 1 · · · F and the length is defined to be . For the SDP case, they showed that the bound can be refined to S n + − 2, which matches the bound discussed in [7], since S n + = n + 1. If K = K n 1 × · · · × K n m , then the largest chain of faces of K * has length 2m + 1.…”
Section: The Number Of Directions Needed To Approach Ksupporting
confidence: 72%
“…Recently, Liu and Pataki generalized the results in [7] and showed that the dimension of L +c can be taken to be less or equal than K * −1, see items (ii) and (iii) of Theorem 9 in [5]. The quantity K * corresponds to the length of the longest chain of faces of K * .…”
Section: The Number Of Directions Needed To Approach Kmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, detection of infeasibility is a complicated task. Some interior point methods, such as the one discussed in [30] by Nesterov, Todd and Ye, are able to obtain a certificate of infeasibility if the problem is dual or primal strongly infeasible, but the situation is less clear in the presence of the so-called weak infeasibility [22]. These issues are also discussed by Karimi and Tunçel in [14], in the context of their software DDS (Domain-Driven Solver) [13,15].…”
Section: Background and Previous Workmentioning
confidence: 99%
“…This term is referring to inconsistent problems whose decision problem is ill-posed. For more details, see [31][32][33] and the references therein. For reasons of simplicity, in the following we assume the problems to be either consistent or strictly inconsistent.…”
Section: Cone-lps With Non-degenerate Unique Solutionsmentioning
confidence: 99%